Virtual Tour 360-Degree Sebagai Media Informasi Pura Jagatnatha Denpasar Berbasis Website - I GEDE WIRYA MAHENDRA NANDANAWANA PUTRA WIRYA; Putu Gede Maha Vivaldi Pradnyana; Dharma Prasetya Irawan (Lembaga Dongan Dosen, 2025)
Jagatnatha Temple is one of the largest temples in Denpasar, holding significant spiritual, cultural, and historical value. However, tourists from outside Bali often face challenges in accessing and learning more about this temple. With the advancement of digital technology, the use of Virtual Reality (VR) and 360-degree virtual tours has emerged as an innovative solution in the tourism industry. This study aims to develop an immersive and informative 360-degree virtual tour prototype based on the presence theory to introduce Pura Jagatnatha to a wider audience. This research applies the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. The initial stage involves data collection through observations and interviews with temple managers and tourists to understand user needs. The define stage identifies key issues related to limited access to information and digital tourism experiences. In the ideate stage, an interactive and educational virtual tour design concept is developed. The prototype stage produces an initial version of the virtual tour, while the test stage evaluates user experience and effectiveness. The outcome of this study is a website-based 360-degree virtual tour prototype, enabling users to explore Pura Jagatnatha digitally with an interactive experience enriched with visual and audio information about its history, architecture, and cultural significance. This virtual tour is expected to serve as an effective promotional and educational tool in preserving Bali's cultural heritage.